A typology of social procurement champions in the construction and engineering industry. Issue 5 (4th May 2022) - Loosemore, Martin; Keast, Robyn; Barraket, Jo
Abstract: Social procurement is re-emerging as an innovative collaborative policy tool for governments around the world to leverage their construction supply chains to help them address intransigent social problems such as long-term unemployment. Such policies challenge deeply rooted institutional norms and structures in the construction industry and research shows that they are being championed by a small and largely undefined group of social procurement professionals who suffer significant role conflict and ambiguity. Contributing new insights to this nascent research, this paper traces etymological definitions of champion roles, merging them with organisational theory to present a new typology of social procurement champions in the construction industry. Drawing on a thematic analysis of snowballed interviews with fifteen recognised champions of social procurement in the Australian construction industry, findings highlight four distinct types of social procurement champion: champions of organisations ; champions of the concept ; champions of people ; and champions of a solution . It is found that there is no one pure type of social procurement champion. Rather, champions have to adapt their social procurement roles to the highly dynamic and varied organisation contexts in which they operate. These findings advance the emerging social procurement debate within and outside construction by highlighting the many different roles which are needed to implement social innovations like social procurement into a project-based industry like construction. It is concluded that organisations which see this as one person's responsibility are likely to fail in implementing these new policy reforms.